Optimization and fouling mechanism of a thermophile submerged MBR (TSMBR) pilot plant for wastewater treatment in a paper mill. (June 2017) - Cramer, Michael; Kloth, Stephan; Tränckner, Jens
Highlights: Verifying a thermophile submerges MBR in pilot-scale under realistic conditions. Investigation of membrane fouling under thermophile conditions. Identifying of optimal conditions for a full-scale installation. Recirculation of permeate for improving the water footprint is possible. Abstract: The state-of-art is a mesophilic treatment of wastewater in paper mills without reuse due to the high water quality requirements. Thermophilic biological treatment could save a large amount of thermal energy, but the major obstacle of a reuse are the poor sludge settling properties under thermophile conditions, leading to insufficient water quality if conventional gravimetric phase separation is applied. MBR technology is a promising alternative which allows a recirculation of treated water for improving the water and energy footprint. So far, there is only limited experience with thermophilic MBR at the time. In this study, a thermophilic MBR with a submerged membrane (TSMBR) was operated to treat wastewater from a paper mill with a COD concentration of 25–30 g L −1 . The TSMBR was integrated into the operational process of the paper mill. Research questions were the influence of suspended solids, food to microorganism ratio (F/M ratio), cross-flow-aeration and filtration flux to the fouling of the membrane. Applying the critical flux concept, optimal operating conditions and costs for a future economic full-scale implementation could be derived. Key results are inter alia a sub-critical flux of below 10 L m −2 h −1 is recommended for long-time durability of the membrane for minimizing the irreversible fouling and the permeability decrease. A chemical cleaning does not change the critical flux, but improves the permeability of the membrane significantly. The TSMBR suffered from increasing fouling at a cross-flow-aeration of below 0.6 m 3 m −2 h −1 and a concentration of suspended solids of above 14 g L −1 . A stable process and cleaning could only be ensured by a F/M ratio of below 0.4 gCOD gMLSS −1 d −1 . Higher values result in an increased cake layer formation and intensive foaming.